Faktor-Faktor yang Mempengaruhi Keputusan Wisudawan Muslim menggunakan X-Banner Kelulusan (Studi Kasus Wisudawan FEBI UINSU) - Rudy Rifalgi; Andri Soemitra (Jurnal Ilmiah Ekonomi Islam, 2023)
Purchasing decisions from consumers to buy a product are an integral part of a company's products and various factors can determine the existence of a decision on the purchase, such as quality, price, motivation, and interest. Through the application of multiple linear regression analysis methods, this study aims for analyzing and knowing the effect of the variables of quality, price, motivation, and interest on consumer decisions to use the X-Banner Graduation. The object of research analysis was carried out on FEBI UINSU graduates. The results of the analysis show that the variables of interest, motivation, quality, and price have a significant effect on the decision variables. This is stated through the probability value that is owned by the interest and quality variables of 0,000, then the price variable of 0,004 which is smaller than the significance level of 0,01 (1%), while the motivational variable is 0.015, which is smaller than the significance level of 0,05 (5%). On another side, the variables of interest, motivation, quality, and price have a correlation or relationship to the influence of the decision variables that have a positive correlation. This proves that a consumer's decision to consume a product is influenced by several factors that do not only come from internal factors (within the consumer) such as interest and motivation, but there are also external factors from the product to be consumed as well, such as the price and quality of the product as well can influence consumer decisions.